Effects of applying different soil conditioners on the yield and heavy-metal content of Edamame (Glycine max (L.) Merr.) - Huang Dongfeng; Wang Limin; Chen Shiping (EPJ Web of Conferences, 2025)
A field plot experiment was conducted to test the influences of six different soil conditioner treatments, including T2: Upland soil conditioner (300kg/hm2), T3: Lvming High Carbon Organic Fertilizer (4500kg/hm2), T4: Soil remediation microbial agent (3000 g/hm2), T5: Nitrates soil conditioner (4500kg/hm2), T6: Calcium-magnesium compound soil conditioner (4500kg/hm2), and T7: ‘Donfenggui’ micro-and nano-silica soil conditioner (30kg/hm2), on the agronomic characters of Edamame, biological yield, the content of heavy metals in soybean grains and the content of available heavy metals in topsoil after harvest of Edamame were studied. Results indicated that compared with T1 (no soil conditioning agent) treatment, T2~T7 treatments could enhance the weight of stems and leaves of soybean plants by 98.57%~154.15%, the fresh weight of roots by 47.53%~344.44%, the soybean shells’ weight by 1.32%~18.47%, and the soybean seeds’ weight by 7.12%~16.06%. T2~T7 treatment enhanced the fresh yield of soybean shells by 4.95%~16.67%, the fresh yield of soybean seeds by 7.12%~16.06%, and could reduce the Cr content of soybean seeds by 61.40%~78.29%, and the Hg content by 0.00%~27.27%. However, for the Pb content of soybean seeds, except for T3 treatment, which showed an increase of 38.24%, other treatments showed an increase in Pb content. Different soil conditioning agents showed a reducing effect, with a reduction range of 20.59% to 53.68%; For the As content in soybean seeds, except for T7 and T3 treatments, other treatments also showed a reducing effect, with a reduction range of 23.08% to 76.92%; It could increase the pH value of the soil after harvesting soybeans by 1.85%~37.04% (except for treatment 5), and the soil available Hg content by 7.69%~23.08%. However, the effects on the increase of soil available As, Pb, Cd, and Cr content vary among different treatments.